2016
DOI: 10.1007/s00210-016-1329-0
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-19 contributes as a protective factor in experimental Th2-mediated colitis

Abstract: Inflammatory bowel disease results from chronic dysregulation of the mucosal immune system and aberrant activation of both the innate and adaptive immune responses. IL-19 is a member of the IL-10 family, and IL-10 plays an important role in inflammatory bowel disease. We have previously shown that IL-19 knockout mice are more susceptible to innate-mediated colitis. Next, we ask whether IL-19 contributes to T cells-mediated colitis. Here, we investigated the role of IL-19 in a mouse model of Th2 cell-mediated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…10) Heterozygous mice were crossed to produce IL-19KO and wild-type (WT) control mice. All mice used were 8-15 weeks old.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10) Heterozygous mice were crossed to produce IL-19KO and wild-type (WT) control mice. All mice used were 8-15 weeks old.…”
Section: Methodsmentioning
confidence: 99%
“…7) We previously generated IL-19 deficient (IL-19 knock out (KO)) mice that demonstrate, in vivo, the importance of inflammatory bowel disease and, in vitro, the significance of macrophage function. [8][9][10] [17][18][19] The psoriatic epidermis has high IL-19 expression, 19) and IL-19 released by keratinocytes upregulates the production of keratinocyte growth factor from CD8 + T cells, which form a positive feedback loop that exacerbates psoriasis. 18) Thus, IL-19 regulates the development of psoriasis through the facilitation of the Th1 response.…”
Section: )mentioning
confidence: 99%
“…Recent studies have shown that IL-19 was produced by keratinocytes [3,4], epithelial cells [5][6][7][8], macrophages [9,10], B cells [11,12], and vascular smooth muscle cells [13]. Our previous studies showed that IL-19-knockout (KO) mice were more susceptible to experimental acute colitis induced by dextran sulfate sodium, TNBS, and oxazolone [10,14,15]. These results indicate that IL-19 plays as the anti-inflammatory effector.…”
Section: Introductionmentioning
confidence: 93%
“…We used IL-19KO mice on a BALB/c background [11,12]. Heterozygous mice were crossed to produce IL-19KO and WT control mice.…”
Section: Micementioning
confidence: 99%